PERAN LEMBAGA PEMBIAYAAN SYARIAH DALAM MENDUKUNG KEMANDIRIAN EKONOMI MASYARAKAT DESA PAYAGELI KABUPATEN DELI SERDANG - Feby Salsabila Dasri; Nabila Nasywa; Nur Atikah; Muhammad Ikhsan Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze the role of Islamic bank financing institutions in supporting the economic independence of rural communities. Using a qualitative approach through interviews with local entrepreneurs, the study found that Islamic-based financing not only provides capital access but also builds responsibility, honesty, and blessings in economic activities. Islamic financial institutions play a strategic role in empowering rural MSMEs through profit-sharing and integrated financial education programs. The findings show that Islamic financing support increases local business productivity, enhances income, and strengthens sustainable rural economic independence.